Sistem Antrian Online PT. Bank Negara Indonesia TBK Kantor Cabang Parigi - Abdi Samuel Mango; Danny Manongga (Maranatha University Press, 2017)
Abstract – Kebutuhan akan kemudahan pelayanan yang di dapatkan oleh Demand for ease of service in getting by the public from the World the Banking, has its own contribution hearts everyday life. Regardless of these advantages, the banking sector is also characterized by shortages arising from the application of the procedures used, especially within the PT. Bank Negara Indonesia TBK Parigi Branch Office is one branch of PT. Bank Negara Indonesia Manado region that wants continue to improve the pattern of banking services. The situation can be seen from the number of stacking of customers queuing for services provided by the Bank. Thus, this study will be focused on the simulation and implementation of Queue System Online at PT. Bank BNI branched office TBK Parigi. The aim of the implementation of this system is to reduce the accumulation of customers that can not be predicted. This study resulted in an online queue system that serves to reduce the number of queues that can not be predicted. Based on the application, there are advantages and disadvantages of such a system. Keywords— Queues, bank, queuing systems, queuing systems online.